Características epidemiológicas, clínicas y terapéuticas de los niños con bronquiolitis aguda en el Hospital Belén de Trujillo durante el periodo 2008 - 2012 - Romero Martínez, Glenn Miguel (2016)
Identify the epidemiological, clinical and therapeutic characteristics of children hospitalized with acute bronchiolitis in our environment. Material and Methods: A descriptive-retrospective study of children under 2 years hospitalized in the Pediatric Service of Hospital Belén of Trujillo diagnosed with acute bronchiolitis, during the period 2008-2012. Results: Of 110 children, most had less than 1 year of age (88.2%) were eutrophic (92.7%) were males (56.4%) and hospitalization time 3 to 7 days (78.1%.). History of not cyanotic congenital heart disease and premature birth was found in 2.72% and 1.81% respectively; and 84.5% were discharged improved. The symptoms noted were cough (89.1%) and rhinorrhea (77.3%) and the signs were print runs, wheezing, and tachypnea with 93.7%, 76.4% and 70% respectively. Oxygen saturation was recorded in low percentage of cases and 64.5% had a mild bronchiolitis severity. Regarding treatment: 57.4% received oxygen therapy; adrenaline indicated with hypertonic saline at 3% (72.5%); and physiological saline (27.7%). Salbutamol was indicated with MDI (41.8%) with hypertonic saline at 3% (38.8%) and physiological saline (19.4%); 30.9% received therapy with inhaled hypertonic saline 3%. Conclusions: Most children hospitalized for acute bronchiolitis were younger than 1 year, eutrophic, males, with mean hospital stay of 3 to 7 days,. The manifestations highlighted were cough, runny nose, runs, tachypnea and wheezing; the severity was mostly mild. The treatment received was varied